Apparent mineralocorticoid excess: A case of hypertension in a child with delayed diagnosis leading to stroke - Inderpal Singh Kochar; Rakhi Jain; Smita Ramachandran (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
Hypertension in pediatric patients,unlike adults, is mostly secondary to systemic disorders which may be renal,cardiovascular or endocrine, among others.Apparent mineralocorticoid excess (AME) is one such cause of hypertension. It occurs due to congenital defi ciency of 11 beta hydroxysteroid dehydrogenase type 2(11HSD 2) which responsible for conversion of cortisol to cortisone [1].